IMPLEMENTASI MEDIA PEMBELAJARAN GAME ONLINE EDUKASI BERBANTUAN TELEPON PINTAR SMARTPHONE PADA PEMBELAJARAN PENDIDIKAN PANCASILA SEKOLAH DASAR KELAS II DI SDN 2 CITEKO PLERED PURWAKARTA - Jamilatu Kudsiah; Agus Muharam; Gemi Gustiani; Ihsan Rizali (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study was motivated by the need for innovative learning media to enhance student engagement in Pancasila Education at the elementary school level, one of which is through smartphone-assisted educational online games. The study aimed to describe the implementation of this learning media, determine students' responses and participation, and identify supporting and inhibiting factors in its implementation in Grade II Pancasila Education at SDN 2 Citeko. This study employed a qualitative descriptive approach with subjects consisting of the Grade II teacher and 25 students. Data were collected through observation, interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the implementation of the learning media was carried out according to the learning stages and was able to increase students' enthusiasm, participation, collaboration, and understanding of the symbols and meanings of the Pancasila principles. Supporting factors included students' learning interest, teacher and school support, and availability of learning devices, while inhibiting factors included limited smartphones, unstable internet connection, and limited instructional time.